2018
DOI: 10.1007/s11356-018-2042-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar-applied iron complexed with lysine on growth and cadmium (Cd) uptake in rice under Cd stress

Abstract: Contamination of soils with cadmium (Cd) is a serious problem worldwide. Rice (Oryza sativa L.) is reported to accumulate relatively higher Cd contents in consumable parts and is considered a main source of Cd toxicity to humans from rice-derived products. The aim of this pot trial was to investigate the effect of foliar-applied iron (Fe) complexed with lysine on growth, photosynthesis, Cd concentration in plants, oxidative stress, and activities of antioxidants of rice in soil contaminated with Cd. Rice seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 45 publications
5
34
0
Order By: Relevance
“…It is also found that CuO NPs decreased As uptake in rice by removing As from the solution with the precipitated complexes and consequently (Wang et al 2019). In addition to As, it is previously reported that ZnO NPs reduced the Cd concentration in wheat and rice (Bashir et al 2018, Rizwan et al 2019a. The application of ZnO NPs increased the Zn concentrations in rice shoots and roots (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…It is also found that CuO NPs decreased As uptake in rice by removing As from the solution with the precipitated complexes and consequently (Wang et al 2019). In addition to As, it is previously reported that ZnO NPs reduced the Cd concentration in wheat and rice (Bashir et al 2018, Rizwan et al 2019a. The application of ZnO NPs increased the Zn concentrations in rice shoots and roots (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, the application of Fe complex with lysine (lys) greatly reduces the toxicity induced by heavy metals stress. Fe complex with lys significantly reduced the Cd stress by improving rice growth, photosynthesis and the antioxidant system [45]. Large amounts of heavy metals in plant organs seriously affected the quality of their vegetative characters.…”
Section: Introductionmentioning
confidence: 98%
“…Because Fe is an essential micronutrient for proper plant growth and development, it plays a crucial role in plant metabolism in enzymatic and metabolic processes [1,43,44]. Conversely, Fe deficiency significantly alters the morpho-physiological characteristics of plants and results in stunned plant growth and biomass [45]. Nevertheless, the application of Fe complex with lysine (lys) greatly reduces the toxicity induced by heavy metals stress.…”
Section: Introductionmentioning
confidence: 99%
“…They are the building units of proteins, as the main component of living cells that have vital roles in many cell metabolic reactions (Kielland 1994;Rainbird et al 1984;Jones and Darrah 1993). In addition, amino acids have various important biological functions in plant cells including detoxification of toxins and heavy metals (Hussain et al 2018;Rizwan et al 2017;Bashir et al 2018), optimizing the nutrient uptake, translocation and metabolism, vitamin biosynthesis, growth biostimulation, creating higher tolerance to environmental stresses such as drought, salinity and cold conditions, as well as in the synthesis and production of aminochelate fertilizers (Jeppsen 1991;Sharma and Dietz 2006;Souri and Hatamian 2019).…”
Section: Introductionmentioning
confidence: 99%